EMPOWERMENT SDM MELALUI PENDAMPINGAN MOTIVASI DAN LITERASI KEORGANISASIAN PADA ORGANISASI MAHASISWA ERA SOCIETY 5.0. - Iing Sri Hadiningrum; Nur Azizurrahman Azizurrahman; Ahmad Yani; Dimas Bagus Rozaqqi; M. Adi Trisna Wahyudi (Jurnal Inovasi Pengabdian Masyarakat, 2025)
This article discusses a Community Service Program (PKM) entitled Human Resource Empowerment through Motivation and Organizational Literacy Assistance in Student Organizations in the Society 5.0 Era. The program is motivated by the low managerial capacity and motivation of student organization members in managing programs, facing digitalization challenges, and developing leadership potential amid the demands of Society 5.0. The implementation method adopts a case study approach through mentoring stages consisting of (1) organizational needs identification, (2) preparation of motivation and organizational literacy modules, (3) interactive training, and (4) sustainability evaluation. The results indicate significant improvements in intrinsic motivation, organizational communication skills, and student organizational literacy. HR empowerment outcomes are reflected in increased active participation, enhanced leadership capacity, and organizational program sustainability. The article concludes with strategic recommendations for student organizations to become more adaptive, innovative, and competitive in the Society 5.0 era.